Tumor-triggered personalized microRNA cocktail therapy for hepatocellular carcinoma. (14th October 2020) - Shao, Shiyi; Hu, Qida; Wu, Wangteng; Wang, Meng; Huang, Junming; Zhao, Xinyu; Tang, Guping; Liang, Tingbo
Abstract : miRNA cocktail therapy based on pH-responsive nanoparticles featuring PEG detachment and size transformation is a potential strategy for HCC treatment. Abstract : As one of the most malignant primary cancers, hepatocellular carcinoma (HCC) still lacks an efficient therapeutic strategy to date. Here, we developed a polymer-based nanoplatform PEI-βCD@Ad-CDM-PEG (PCACP) for functional microRNA (miRNA) therapy. PCACP exhibits excellent stability in physiological solutions, but sensitive PEG detachment and size transformation in an acidic tumor environment due to the breakdown of pH-responsive linkages, promoting tumor penetration and cellular uptake of nanoparticles, further facilitating transfection efficiency due to the proton sponge effect of polycations. We present a novel miRNA cocktail therapy by encapsulating miR-199a/b-3p mimics (miR199) and antimiR-10b (antimiR10b) into PCACP for eliminating HCC. Validated by qRT-PCR, immunoblotting and immunohistochemistry, compared with miR199 or antimiR10b delivered alone, miR-cocktail therapy substantially inhibits HCC cell proliferation and tumor growth by targeting mTOR, PAK4, RHOC and epithelial–mesenchymal transition (EMT) pathways both in vitro and in vivo (i.v. injection). Furthermore, we proposed personalized miR-cocktail therapy by adjusting the encapsulated miRNA formula according to the miRNA profiling of a patient's tumor sample. The personalized PCACP/miR-cocktail system exhibits significant tumor suppression and multitarget regulation on patient derived xenografts (PDXs), representing a notable effect improvement over conventional gene therapy. The tumor-acidity-cleavable PCACP/miR-cocktail system, with loaded miRNA controllability and high transfection efficiency, is a promising personalized therapeutic strategy for future HCC treatment.